ARDUINO BASED SYSTEM TO MEASURE SOLAR POWER - ASULA, MUDE SREENIV; RANJITH; VANISREE, K. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this project is to design and build a solar energy monitoring system that makes use of Arduino Board technology to accomplish its objectives. A number of parameters were assessed in this research, including thermal conductivity, light intensity, voltage conductivity, and current conductivity, among others. A temperature sensor was used to keep tabs on the temperature of the room. The intensity of the light was measured with the help of a light dependent resistor (LDR) sensor. Consequently, we employed a voltage divider to measure the voltage since the voltage generated by the solar panel is too high for the Arduino, which is functioning as the receiver in this experiment. To finish it, we used a current sensor module that was capable of detecting the current generated by the solar array to take a reading on the current. The Arduino was given these settings as input values, and the result was shown on a Liquid Crystal Display (LCD) screen on the computer. On the LCD display screen, the temperature, the light intensity, the voltage, and the current amounts are all shown in real time. In order to display the result on an LCD screen, the Arduino must transform the analogue input of a parameter to a digital output and then back to analogue. This project will also feature a design that will ensure that the device casing is portable and easy to move, amongst other things.